Long-distance Lapita pottery transfers and ancient social relationships: A case study from the St. Maurice-Vatcha (KVO003) Lapita site on Île des Pins, New Caledonia (Southern Melanesia). (December 2020) - Chiu, Scarlett; Killick, David; Sand, Christophe; Su, Yuyin
Highlights: Petrography shows transport of large quantity of pots more than 400 km during Lapita era. No local production has been recognized at Vatcha so far. Vatcha people preferred long-distance relationships instead of exchange with people in closer Lapita sites. Abstract: In this paper we present petrographic analyses of 68 Lapita pottery sherds excavated from the St. Maurice-Vatcha Lapita site located on the southeast coast of Île des Pins, New Caledonia and dated between 950 and 800 cal BC. Nearly two-thirds of these samples were without doubt made in the Diahot River valley region at the northwestern end of the main island (Grande Terre) some 400 km away from Île des Pins. Samples from another major geological region on the west coast of Grande Terre have also been identified, but no local production has been recognized so far. We propose that long-distance pottery transportation between the Diahot River valley settlers and those who inhabited Île des Pins may indicate: (1) an early establishment of Lapita settlements (so far undiscovered) in the Diahot region before occupation of Île des Pins; and (2) a persistent and preferred relationship between Île des Pins and the Diahot River valley. Other communities located on various parts of Grande Terre also established relationship with inhabitants of St. Maurice-Vatcha, but these do not appear to have been as intensive or long-lasting as those from the Diahot River valley. Surprisingly, Lapita people of the nearby Loyalty Islands – probably the earliest Lapita settlers of the entire New Caledonia archipelago – do not appear to have supplied pottery to those occupying Île des Pins during this time period.